TINJAUAN KEBUTUHAN TENAGA INSTALASI REKAM MEDIS BERDASARKAN ANALISIS BEBAN KERJA KESEHATAN DI RUMAH SAKIT PUSAT OTAK NASIONAL PROF. DR. dr. MAHAR MARDJONO JAKARTA - Meliana; Adhe Ramadhan (APIKES Bhumi Husada Jakarta, 2023)
Workload analysis is a method used to determine the amount of time, effort and resources required to carry out organizational tasks and functions. The results of the initial observations. Researchers took the example of a monthly report in October, November, December 2021, it was found that the monthly report for that month experienced a delay in completion. The report that was supposed to be completed at the beginning of the following month was only completed in the middle of the following month, because some work from the medical record installation had not been completed, such as from the coding and analysis of the completeness of the medical record. Research objectives is To calculate the need for personnel in the medical record installation at the Rumah Sakit Pusat Otak Nasional Prof. Dr, dr. Mahar Mardjono Jakarta. Research methodology is Descriptive with a quantitative approach with research subjects 11 medical record officers and the object of research is a review of the needs of medical record installation personnel based on workload analysis. The results of the study Every job in the medical record installation already has an SOP, the available working time is 5 working days in 72000 minutes / year, the result of calculating the number of Human Resouce Health needed is 12 people.Human Resouce Healt needs in medical record installations are 12 people., Keywords : Medical Record , Work Loard Analysis , Human Resouce Health